2001
DOI: 10.1002/jcla.5
|View full text |Cite
|
Sign up to set email alerts
|

Negative interference of bilirubin and hemoglobin in the MEIA troponin I assay but not in the MEIA CK‐MB assay

Abstract: Troponin I is a sensitive and specific marker for the diagnosis of myocardial infarction. Several commercially available immunoassays measure the concentration of troponin I in serum. The microparticle enzyme immunoassay (MEIA) for troponin I (Abbott Laboratories, Abbott Park, IL) is widely used in clinical laboratories, including our hospital laboratory. We studied the effect of bilirubin and hemolysis on the MEIA for troponin I and compared our assay with a newly available chemiluminescent assay (CLIA) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
2
7
1
2
Order By: Relevance
“…It has been previously demonstrated that hemolysis has less effect on mass assays than activity based methods but the degree and the direction of this interference is still contradictory in the literature [23]. Many studies has claimed that hemolysis has not any effect on mass assays except at very high Hb values [24][25][26]. In contrast, Donnely detected positive interference due to hemolysis in CK-MB mass assays [27].…”
Section: Discussioncontrasting
confidence: 38%
“…It has been previously demonstrated that hemolysis has less effect on mass assays than activity based methods but the degree and the direction of this interference is still contradictory in the literature [23]. Many studies has claimed that hemolysis has not any effect on mass assays except at very high Hb values [24][25][26]. In contrast, Donnely detected positive interference due to hemolysis in CK-MB mass assays [27].…”
Section: Discussioncontrasting
confidence: 38%
“…They may also result from fluid therapy given to patients (28 ). One report of a false-negative cTnI result was attributed to circulating cTnI autoantibodies (29 ), and bilirubin and hemoglobin have been reported to cause negative interference in certain cTnI assays (30 ).…”
supporting
confidence: 39%
“…Numerous assaydependent false-positive results for troponin assays have been reported, the majority of which were caused by heterophilic antibodies (17 ) or rheumatoid factor (18 -20 ). False-negative results have been attributed to bilirubin, hemoglobin (21 ), and in one case, to circulating cTnI autoantibodies (22 ). When performing recovery studies with a cTnI immunoassay, we previously observed frequent negative interference from a serum-and plasmaderived component found in both healthy individuals and patients with acute coronary syndromes (23 ).…”
mentioning
confidence: 42%